2020
DOI: 10.3390/microorganisms8030354
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Probiotic Potential and Safety Evaluation (Hemolytic, Cytotoxic Activity) of Bifidobacterium Strains Isolated from Raw Camel Milk

Abstract: The present study was designed to isolate Bifidobacterium strains from raw camel milk and to investigate their probiotic characteristics. Among 35 isolates, 8 were identified as Gram-positive, catalase negative, non-spore forming, non-motile and V or Y shaped rods. B-2, B-5, B-11, B-19 and B-28 exhibited good survival at low pH and high bile salt concentration. Most of the isolates were resistant to nalidixic acid, fusidic acid, polymyxin B, neomycin, streptomycin, gentamicin, rifampicin and kanamycin. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 70 publications
9
77
1
Order By: Relevance
“…As mentioned in recent studies, the antimicrobial properties of Bi dobacterium are important probiotic features (29,30) that showed in the present study in a selected strain isolated from chicken intestine, and antimicrobial effects were seen on all three pathogens S. enterica, E. coli, and P. vulgaricus using the disc diffusion method. Such a feature has been reported in other studies (31,32).…”
Section: Discussionsupporting
confidence: 68%
“…As mentioned in recent studies, the antimicrobial properties of Bi dobacterium are important probiotic features (29,30) that showed in the present study in a selected strain isolated from chicken intestine, and antimicrobial effects were seen on all three pathogens S. enterica, E. coli, and P. vulgaricus using the disc diffusion method. Such a feature has been reported in other studies (31,32).…”
Section: Discussionsupporting
confidence: 68%
“…As mentioned in recent studies, the antimicrobial properties of Bi dobacterium are important probiotic features (Monteiro et al, 2019;Yasmin et al, 2020) that showed in the present study in a selected strain isolated from chicken intestine, and antimicrobial effects were seen on all three pathogens S. enterica, E. coli, and P. vulgaricus using the disc diffusion method. Such a feature has been reported in other studies (Invernici et al, 2018;Prabhurajeshwar & Chandrakanth, 2019).…”
Section: Discussionsupporting
confidence: 68%
“…The term “probiotic” refers to microorganisms that benefit the host when administered in appropriate quantities (Hotel, 2001; Hill et al, 2014; Roberfroid, 2000). The best probiotics are of human origin that is safe and does not harbor genes associated with antibiotic resistance, pathogenicity, or virulence factors (Yasmin et al, 2020). At the same time, they must be able to survive under intestinal conditions (e.g., acid pH, enzymes, and bile salts) (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%